PENGARUH PUPUK KASCING DAN MIKORIZA TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN BAWANG MERAH (Allium ascalonicum L) - Ansyar, Ihsan Azzam; Silvina, Fetmi; Murniati, Murniati (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
This research purposed to find out the interaction of earthworms vermicompost and mycorrhiza on the growth and production of shallot (Allium ascalonicum L) and to get a best dose the combination earthworms vermicompost and mycorrhiza on the growth and production of shallot. The research was conducted on randomized block design (RBD) factorial consisting of two factors. The first factor was the earthworms vermicompost that consists of 4 levels that is K0: 0 ton/ha, K1: 15 ton/ha, K2: 20 ton/ha, K3: 25 ton/ha and the second factor was mycorrhiza consists of 2 levels that is M0: 0 g/plant, M1: 10 g/plant. Parameters observed relative growth rate, plant dry weight, number of leaves per clump, the number of tubers per clump, convolution of tubers per clump, the weight of fresh roots per clump, tuber weight dry shelf per panicle and weight of dried tubers shelf per plot carried out at the end of the research, data were statistically analyzed by ANOVA and followed by Duncan's multiple range test on 5% level. The results showed that earthworms vermicompost and mycorrhiza showed significant interaction observations on all parameters except the number of tubers per hill. Based on the research granting earthworms vermicompost treatment combined 15 ton/ha and mycorrhiza 10 g/plant is the best dose in getting the growth and production of onion.Keywords: Shallot, Earthworms vermicompost, Mycorrhiza,